Service Providers' Perspectives on Barriers of Healthy Eating to Prevent Obesity among Low-income Children Attending Community Childcare Centers in South Korea: A Qualitative Study. Issue 3 (3rd May 2020) - Park, Jiyoung; Ten Hoor, G. A.; Cho, Jeonghyun; Kim, Soobin
ABSTRACT: This study aimed to identify individual and socio-ecological barriers in managing healthy eating among low-income children from the perspective of community childcare (CCC) center workers (n = 18) through focus group interviews. They perceived the increase in obesity among low-income children. The interviews revealed that the child's eating habits are affected by not only individual determinants including self-regulation and risk awareness but also environmental factors such as family, CCC centers, policy and social structure. To enhance children's health and behavior, it is necessary to consider the interactions among systems at a variety of levels, for example, local community and health care policies.